Pelatihan Perpajakan Umkm Pada Lingkungan Universitas Dirgantara Marsekal Suryadarma - Bintang B. Sibarani; Putu Rani Adnyani Asak; Zeta Ayleita R.V; Rio Johansen Tumanggor; Muhamad Ikmal Ramadhan (Jurnal Abdimas Perbanas, 2022)
This Community Service (PkM) aims to assist Micro, Small and Medium Enterprises (MSMEs) within UNSURYA in compiling tax reports related to MSMEs, which is the calculation of MSME Income Tax in accordance with the rates determined by the latest tax laws contained in harmonization. tax regulations and training for filling out the form 1721. This training is a continuous activity that is held in collaboration between the Faculty of Economics, Accounting Study Program, UNSURYA and the DJP of the East Regional Office. Assistance in the form of online training using the Zoom Meeting application. During the training, the discussion between the resource persons and the participants was guided by a moderator. As feedback and to find out the participants' understanding, a survey was conducted on the participants using a questionnaire on the google form. Based on the results of the evaluation after the PkM implementation, it showed that the PkM participants expressed satisfaction with the resource persons, the implementation of the activities, and the PkM objectives were achieved because the participants felt that they had benefited in the form of knowledge and skills about calculating MSME Income Tax (PPh) and the procedure for filling out formular 1721. Implications of PkM for MSMEs , Lecturers, Students, FE-UNSURYA and the Government.